Preparing for the worst incorporating downside risk in stock market investments - Vinod Hrishikesh D; Reagle Derrick P (New Jersey John Wiley, 2005)
This book begins by explaining the current treatment of stock market risk and methods of lowering that risk. The authors then show that many types of asymmetry of stock returns or investor reactions cause the existing theory to fail. They present the the
Keywords: Investments; Risk management; Stocks